Innovation acceleration : - Kuratko, Donald F. (Pearson, 2012)
Innovation Acceleration: Transforming Organizational Thinking helps readers develop an understanding of innovative organizations, the specific processes involved in corporate innovation, and how to assess an organization’s readiness for entrepreneurial activity and innovation.